Socio-Demographic Determinants of Hospitalization Severity Among Type 2 Diabetes Mellitus-Related Hospitalization Visits in Indonesia: A Cross-Sectional Analysis of Using BPJS Health Secondary Data, 2023 - Putri, Nadia; Adisasmita, Asri C.; Fitria, Fitria; Anggraini, Sely (Jurnal Epidemiologi Kesehatan Indonesia, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic disease with high prevalence and contributes significantly to the burden of inpatient care in Indonesia. The severity of T2DM-related hospitalization as classified under the INA-CBGs system, is an important indicator for assessing disparities in access to care and the health system’s response to vulnerable populations. This study aims to analyze the relationship between socio-demographic characteristics and the severity of T2DM-related hospitalization visits based on 2023 Social Security Administering Body for Health (BPJS Health) data. This study employed a cross-sectional design using secondary data from the 2023 BPJS Health Sample Data. The unit of analysis was hospitalization visits. The study included inpatient hospitalization visits with a diagnosis of T2DM (ICD-10: E11). Univariate and bivariate methods were conducted, including chi-square tests and ordinal logistic regression was estimated using cluster-robust standard errors. Hospitalization severity was categorized based on the INACBGs classification (mild, moderate, severe). Among 431 T2DM-related hospitalization visits, age >45 years (OR = 2.17; p = 0.035), divorced status (OR = 2.33; p = 0.021), and lower middle socioeconomic status (OR = 1.54; p = 0.046) were significantly associated with higher INA-CBGs hospitalization severity. Gender, inpatient care class, and type of healthcare facility ownership were not statistically significantly associated with hospitalization severity. These findings highlight the importance of the health system's response to the social determinants reflected in INA-CBGs–based hospitalization severity among T2DM-related visits. Targeted and multisectoral interventions are needed to reduce disparities and improve service quality for socially vulnerable groups. Keywords: Type 2 diabetes mellitus, hospitalization severity, socio-demographics, BPJS Health